IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA DI KOTA JAYAPURA PROVINSI PAPUA - ANGGRESU, GRETHA; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
The existence of street vendors around the Kelapa II Entrop considered to be the cause of traffic congestionand disturb the beauty of the City. Along with the increase in street vendors Departement of industry andcommerce specifically the trade department do arrangement to street vendors by registering also socializingand prepare a place for traders. The purpose of this study to find out how the street vendor arrangementpolicy. The method used this study is a qualitative by using method of observation,interviews,anddocumentation. Result of the study shows that policy implementation of the street vendors arrangementatnot maximal, this is due to several problem and obtacles that keep trader from selling.Keywords : implementation, policy, street vendors arrangement